1977
DOI: 10.1021/bi00635a001
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of human J chain: isolation and characterization of tryptic and chymotryptic peptides of human J chain

Abstract: Human J chain isolated from the plasma of a patient with Waldenstrom's macroglobulinemia was subjected to extended and limited digestion with trypsin and chymotrypsin. The digests were fractionated by combination of column chromatography and high voltage paper electrophoresis. Peptide purity was established by their amino acid analysis and a single amino terminal residue. All the necessary peptides which would provide the total primary structure of molecule were thus obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Collins et al [6] conducted mass-spectrometry-based biomarker discovery using ALS CSF and reported that FSTL4 was decreased in ALS CSF in consistency with our result. JCHAIN, which was increased in ALS in our study, is a protein component of immunoglobulins A and M working as a glue for the formation of multimeric immunoglobulins [58]. However, its relationship with ALS is not known yet.…”
Section: Discussionmentioning
confidence: 49%
“…Collins et al [6] conducted mass-spectrometry-based biomarker discovery using ALS CSF and reported that FSTL4 was decreased in ALS CSF in consistency with our result. JCHAIN, which was increased in ALS in our study, is a protein component of immunoglobulins A and M working as a glue for the formation of multimeric immunoglobulins [58]. However, its relationship with ALS is not known yet.…”
Section: Discussionmentioning
confidence: 49%
“…In one, samples were dialyzed against 0.1 M acetic acid at 40C, lyophilized and processed in a B3eckman 890C sequencer with a 1M Quadrol program. Phenylthiohydantion derivatives were identified by high-pressure liquid chromatography as described by Bhown et al (1). In the second procedure, the sample, dialyzed against 10%o acetic acid at 4°C and lyophilized, was dissolved in 0.4 M N,N-dimethyl-N-allylamide/pyridine buffer, attached to isothiocyanato glass (2), and run on a Sequemat model 12 sequencer with a P-6 autoconverter.…”
mentioning
confidence: 99%